Electrochemical Behavior of Metals Used in Drinking Water Distribution Systems: A Rotating Cylinder Electrode's Study (2013)
ABSTRACT: The corrosion behavior of electrolytic copper (>99.5% purity [UNS C11000]), carbon steel (AISI/SAE 1016 [(UNS G10160]), and Type 304 (UNS S30400) stainless steel in neutral tap water was examined by potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) using a rotating cylinder electrode (RCE). The instantaneous corrosion rates determined from polarization curves were 0.2, 15, and 140 ìm y-1 for stainless steel, copper, and carbon steel, respectively. These values were found to be consistent with those reported by the weight-loss method, thereby allowing RCE to be used for the rapid estimation of corrosion rates. Results showed that the corrosion behavior is not directly dependent on hydrodynamic conditions even under turbulent flow. The corrosion resistance does not seem to be related to the intrinsic reactivity of each metal but rather to the oxide film structure on the metal surface. The low resistance of carbon steel, hence, is caused by the formation of a porous layer that does not prevent metal dissolution. In the case of copper, the corrosion process is controlled by the formation of a stable oxide film. Finally, stainless steel showed a very low corrosion rate because of a passive protective layer on its surface.